Control of Main Distribution Material Inventory (MDU) at Pt PLN UP3 Mempawah with Fsn-Xyz and Risk Analysis - Arrahmad Ihsan; Suparno Suparno (Riviera Publishing, 2025)
Main Distribution Materials (MDU) have a vital role in supporting the operational activities of PT PLN UP3 Mempawah, especially in meeting the needs of electricity services for new installations and power changes. The management of MDU inventory that is not optimal often causes problems such as shortage or excess stock due to not taking into account demand uncertainty. This study aims to optimize the inventory management and distribution of MDUs by combining the FSN-XYZ analysis method with the FMEA and FMECA risk assessment approaches. The FSN-XYZ method is used to classify materials based on the frequency of movement and demand variability, while FMEA and FMECA are used to identify potential failures and assess their criticality. The data used in this study came from primary and secondary data, including inventory history and company policies. The results show that most MDU items are classified as Z which has high demand but is unstable, so there is a risk of causing operational disruptions. By implementing an integrated risk-based classification strategy, PLN can prioritize critical items, reduce operational disruptions, and improve cost efficiency. The study also recommends strategies tailored to each category of inventory, such as Just-In-Time for stable materials and a consignment or bundling system for slow-moving materials. The implications of this study emphasize the importance of data-driven adaptive inventory policies in the electricity infrastructure industry that requires high reliability.